2020
DOI: 10.1021/acs.analchem.0c04074
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Hierarchically Micro- and Mesoporous Metal–Organic Frameworks for High-Resolution and High-Efficiency Capillary Electrochromatographic Separation

Abstract: Metal−organic frameworks (MOFs) have been widely applied in a variety of fields. However, most of the developed MOFs are micrometer scale in crystal size and contain only micropores, which will limit the mass transport and diffusion of various analytes into their internal interaction sites, severely restricting the potential of MOFs in separation science. Herein, nanoscale hierarchically porous MOFs (NHP-MOFs) were first explored as a novel MOF-based stationary phase with excellent mass transfer performance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…As shown in Figure and Figure S12, baseline separation of the five types of analytes with high column efficiency, including neutral, acidic, and alkaline compounds, could be easily achieved on all the three MOF-modified columns under their respective optimal conditions. Interestingly, in our previous study, the UiO-66-modified capillary fabricated using the postmodified strategy showed relatively low column efficiency for the separation of two types of aromatic compounds. The distinct difference in the separation effects of the two methods indicated that the preparation method of the MOF coating inside the capillary has a significant impact on the coating quality and electrochromatographic separation performance.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure and Figure S12, baseline separation of the five types of analytes with high column efficiency, including neutral, acidic, and alkaline compounds, could be easily achieved on all the three MOF-modified columns under their respective optimal conditions. Interestingly, in our previous study, the UiO-66-modified capillary fabricated using the postmodified strategy showed relatively low column efficiency for the separation of two types of aromatic compounds. The distinct difference in the separation effects of the two methods indicated that the preparation method of the MOF coating inside the capillary has a significant impact on the coating quality and electrochromatographic separation performance.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, the excellent separation performance and column capacity of Cys-MIL-100­(Fe)@capillary were mainly because of the high porosity and unique pore structure of MIL-100­(Fe). More specifically, compared with the other three MOF-modified columns, the larger pore size of MIL-100­(Fe), which contains mesoporous cages (25–29 Å) and microporous windows (5.5–8.6 Å) simultaneously, contributes to reducing the mass transfer resistance of various analytes entering and leaving its internal cavities, thus greatly improving the electrochromatographic separation performance . In contrast, even though Cys-HKUST-1@capillary had the highest BET surface area, its normalized column capacity was the lowest among all the four capillaries, which might be due to the smallest cavity diameter of HKUST-1.…”
Section: Resultsmentioning
confidence: 95%
“…At the beginning, the uncoated new capillary columns (33 cm total length) were pretreated using the same processes as our previous study. 23 Subsequently, the prepared columns were premodified with Cys and further utilized for the in situ growth of UiO-66-NH 2 nanocrystals via the ICISG strategy. 22 Briefly, ZrCl 4 (8 mg, 0.0343 mmol) and BDC-NH 2 (6.2 mg, 0.0343 mmol) were codissolved in DMF (2 mL) at room temperature to prepare the precursor solution.…”
Section: ■ Experimetal Sectionmentioning
confidence: 99%
“…The fabrication process of UiO-66-NH 2 –IMER is illustrated in Figure . At the beginning, the uncoated new capillary columns (33 cm total length) were pretreated using the same processes as our previous study . Subsequently, the prepared columns were premodified with Cys and further utilized for the in situ growth of UiO-66-NH 2 nanocrystals via the ICISG strategy .…”
Section: Experimetal Sectionmentioning
confidence: 99%
“…Alternatively, smaller voids can be introduced in the MOF crystal network by adding a modulator in the MOF synthesis [ 42 ]. This approach has been explored adding dodecanoic acid in the synthesis of the MOF UiO‐66 (Figure 3a ) [ 43 ]. The resulting nanoscale hierarchically micro‐ and mesoporous MOF (NHP‐UiO‐66) was immobilized on the capillary inner surface and applied as stationary phase for capillary electrochromatography for substituted benzenes obtaining column efficiencies of up to 1.2 × 10 5 plates/m with migration time RSDs lower than 5.8% for intraday, interday, and column‐to‐column comparisons.…”
Section: Metal‐organic Frameworkmentioning
confidence: 99%